Cacat Mental Pada Penyakit Kromoson - Hartono Hartono (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 1985)
Genetic diseases are divided into genic diseases, chromosomic diseases and embryopa shies. There are 23 pairs of chromosomes in each human somatic cell. According to their shape and the location of their centromer, chromosomes are classified into 8 groups, namely group A, B, C, D. E. F and G. Chromosomic diseases are caused by either numerical or structural derangements of chromosomes. Chromosomic diseases cause metabolic disorders during conception until post-natal period. The degree of physical as well as mental disorders depend on the degree of lack or surplus of chromosomic materials. Chromosomic diseases may be lethal. i. e. they can cause spontaneous abortion as well as fetal and neonatal death. Some chromosomic diseases and their IQ scores will be presented here. Special attention will be given to trisomy 13, trisomy 18. trisomy 21, XXX syndrome and XYY syndrome. Key Words : mental defect - chromosomic disease - chromosome classification - IQ score - embryopathies -